1995
DOI: 10.1109/50.365216
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth-doped integrated glass components: modeling and optimization

Abstract: Abstruct-For the integrated optic erbium-doped phosphate silica amplifier, a comprehensive model is presented which includes high-concentration dissipative ion-ion interactions. Based on actual waveguide parameters, the model is seen to reproduce measured gains closely. A rigorous design optimization is performed, and the influence of variations in the launched pump power, the core cross section, the waveguide length, the erbium concentration, and the background losses are evaluated. Optimal design proposals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The quadratic model can be shown theoretically, if migration is assumed sufficiently strong (the kinetic limit) [21] and the model has been supported by some experimental results [4], [23]. Other authors have suggested a cubic model [2], [24].…”
Section: Detailed Model For Homogeneous Upconversionmentioning
confidence: 68%
See 4 more Smart Citations
“…The quadratic model can be shown theoretically, if migration is assumed sufficiently strong (the kinetic limit) [21] and the model has been supported by some experimental results [4], [23]. Other authors have suggested a cubic model [2], [24].…”
Section: Detailed Model For Homogeneous Upconversionmentioning
confidence: 68%
“…For erbium-doped fiber amplifiers, a reduction in gain from 18.3 to 6.9 dB due to quenching is described in [1] for an Er concentration of 6.4 10 m . In erbium-doped silica waveguides for integrated optics, Er concentrations as high as 1.0-2.0 10 m (corresponding to 1.3-2.5 wt.% Er may be necessary to simultaneously ensure sufficient gain and compactness of the components [2], [3], and consequently, quenching is a very serious problem with such devices. For example, a reduction in gain from 37 to 13 dB at an Er concentration of 1.15 10 m is reported in [2].…”
Section: Monte Carlo Simulations Of Homogeneous Upconversion In Erbiumentioning
confidence: 99%
See 3 more Smart Citations